A survey of religious instruction in the public schools of Pangasinan and Dagupan City - Cayabyab, Alfredo Gelli 1915- ([Quezon City University of the Philippines], 1959)
The writer aims to find out whether in the implentation of the religious provision of our Constitution, there are factors that contribute to the alleged failure of religious instruction in the public schools of Pangasinan.
Bibliography: l. 115-117.
Thesis (M.Ed.)--University of the Philippines, 1959
Typescript (carbon copy)
Vita
Keywords: Religious education -- Philippine Islands -- Pangasinan; Religious education -- Philippine Islands -- Dagupan City